The Determinants of Working Children in Urban and Rural Indonesia in 2019 - Achmad T. Nugraha; Priyo M. Waskito; Ahmadriswan Nasution; Gunawan Prayitno (Paspalum: Jurnal Ilmiah Pertanian, 2022)
This study aims to examine the determinants of working children based on individual and environmental factors in urban and rural areas. The study draws on secondary data from various sources, including the March 2019 National Socio-Economic Survey (Susenas), the Indonesia Poverty Profile 2019, the Indonesian Education Statistics 2019, and the Indonesian Child Profile 2020. A multilevel binary logistic regression model was used as the analytical method. According to the study's findings, children have a greater proclivity to work in rural areas than in urban areas. The study's findings also show that children who smoke have a higher proclivity in both urban and rural areas. Further research indicates that individual factors, such as household size as measured by the number of household members, have a more significant influence on the determinants of children working in urban areas. Meanwhile, environmental factors significantly influence the determinants of children working in rural areas, precisely the percentage of children working in the informal sector and the school participation rate of 13-15 years old. The findings show that the determinants of working children in urban and rural areas are similar on an individual level but differ on an environmental level. Based on these findings, the government and related parties must encourage the reduction of smoking behavior in children in urban and rural areas to reduce the number of working children. Accelerating the decline in working children, particularly in rural areas, can increase school participation through improved educational quality and facilities.